A SHRIMP U-PB AND LA-ICP-MS TRACE ELEMENT STUDY OF THE PETROGENESIS OF GARNET-CORDIERITE-ORTHOAMPHIBOLE GNEISSES FROM THE CENTRAL ZONE OF THE LIMPOPO BELT, SOUTH AFRICA - Buick I.S.; Hermann J.; Williams I.S.; Rubatto D.; Gibson R.L. (My University, 2006)
The Central Zone of the Limpopo Belt (South Africa) underwent high-grade metamorphism at ~2.7-2.5 and ~2.03 Ga. Quartz-rich, garnet-, cordierite-, biotite- and orthoamphibole-bearing, feldspar-free gneisses from the western Central Zone reached granulite-facies conditions (~800 °C at ~8-10 kbar) followed by decompression. Garnet from one such sample shows significant zonation in trace elements but little zonation in major elements. Zoning patterns suggest that the early prograde breakdown of REE-rich accessory phases contributed to the garnet trace element budget. Monazite from the sample yields a SHRIMP weighted mean 207Pb-206Pb age of 2028 ± 3 Ma, indistinguishable from a SHRIMP zircon age of 2022 ± 11 Ma previously measured on metamorphic overgrowths on ~2.69 Ga igneous zircon cores. New zircon and monazite formed before, or at, the metamorphic peak, and occur as inclusions in garnet. Monazite appears to have formed through the breakdown of early allanite ± xenotime ± apatite. Trace element zoning patterns in garnet and the age of accessory phases are most consistent with a single tectonometamorphic event at ~2.03 Ga. The plagioclase and K-feldspar-free composition of the garnet-cordierite-orthoamphibole gneisses requires open system processes such as intense hydrothermal alteration of protoliths or advanced chemical weathering. In the studied sample, the ~2.69 Ga igneous zircons show a prominent negative Eu anomaly, suggesting equilibrium with plagioclase, or plagioclase fractionation in the precursor magma. In contrast, the other minerals either show small negative (~2.03 Ga monazite), no (~2.02 Ga zircon and garnet) or positive Eu anomalies (orthoamphibole). This suggests that the unusual bulk compositions of these rocks were set in after ~2.69 Ga but before the peak of the ~2.03 Ga event, most probably while the protoliths resided at shallow or surficial crustal levels. © 2005 Elsevier B.V. All rights reserved.
Keywords: ALTERATION; LA-ICP-MS; LIMPOPO BELT; METAMORPHISM; REE; U-PB AGE